ANALISIS BUKU TEKS TEMATIK TERPADU KELAS IV SEKOLAH DASAR KURIKULUM 2013 - Fajar Suryaningra, Eko; Hakim, Abdul; Purnama Andrian, Retno (Bale Aksara, 2021)
This research is content analysis research that using qualitative approach, with the student's book of grade 4 with the theme 1 Beautiful Togetherness, the instrument is used in this research is researchers themselves supported by other instruments, namely data cards, interviews and documentation. Data analysis technique using research use content analysis. The research result showed if (1) suitability of the material is on a good scale with percentage of suitability is 88,8%, deficiency of 11,2% is in the presentation of illustrations and lack ofpresentation of features that support material, (2) suitability of language theme of the book is in a good scale with percentage of suitability is 96,4% this result is supported by a good language adjustment and supported by rigidity of composing word according to the rules of correct Indonesian language, deficiency of 3,6% affected by relation and integrity between sections, (3) suitability of presentation theme 1 of book is in a good scale with percentage of89,0%, deficiency of 11% is affected by lack variation in presentation, no presentation of the glossary, summary and concept maps, (4) suitability of graphic theme 1 of the book is in a good scale with suitability of percentage is 91,4%, deficiency 8,6% shortfall lies in the presentation of book contents that reduce the tidiness of page utilization and the lack of accuracy and illustration of the concrete